ChemInform Abstract: Pd2+‐Incorporated Perovskite CaPd3M4O12 (M: Ti, V). Issue 17 (4th April 2013) - Shiro, Kentaro; Yamada, Ikuya; Ikeda, Naoya; Ohgushi, Kenya; Mizumaki, Masaichiro; Takahashi, Ryoji; Nishiyama, Norimasa; Inoue, Toru; Irifune, Tetsuo
Abstract Novel A‐site ordered perovskites CaPd3Ti4O12 and CaPd3V4O12 are synthesized (stoichiometric mixture of CaO, PdO, TiO2 or VO2; Au capsule, 15 GPa, 1000°C, 30 min, quenching).